Boswellia dalzielii Methanol Stem Bark Extract Demonstrates Significant Analgesic Activity in Swiss Albino Mice - Abubakar, Hauwau; Tahir, Albashir; Umar, Aminu Kura (Sciences of Phytochemistry, 2024)
Medicinal plants are gaining popularity as safer and more natural alternatives to orthodox medicines for managing health challenges and diseases. One such plant is Boswellia dalzielii, a renowned tree in northern Nigeria extensively used due to its ethnomedicinal importance. To determine the analgesic properties of Boswellia dalzielii methanol extract (BDME), the extract was screened in mice using thermal and acetic acid-induced pain models. The extract's acute toxicity and phytochemical constituents were determined using standard protocols. The results showed that the acute toxicity of the methanol stem bark extract was greater than 2000 mg/kg. Phytochemical screening of BDME revealed the presence of flavonoids, tannins, saponins, and glycosides. The extract, at the dose of 50 mg/kg significantly (p < 0.05) prolonged the pain reaction time at 15 and 30 minutes in the hot plate test, and reduced acetic acid-induced writhing at the 12.5, 25, and 50 mg/kg doses. The analgesic activity of the extract may be attributed to the phytochemical contents. The findings suggest that BDME have analgesic properties and could be beneficial in alleviating painful conditions.